Occupied Territory at the Interstices of the Sacred: Between Capital and Community - Tremlett, Paul-François (Religion and society, 2012)
In the autumn of 2011 and the spring of 2012, the Occupy London protests, informed by the ideal of a moral, territorially defined community, caught the imagination of British and global publics. For a short while, this moral imaginary was mobilized to contest some of the most glaring contradictions of the neo-liberal city. I argue that the Occupy protests in London registered a sense of public outrage at the violation of certain 'sacred' norms associated with what it means to live with others. More concretely, I contend that Occupy London was an experiment initiated to open out questions of community, morality, and politics and to consider how these notions might be put to work. These questions were not merely articulated intellectually among expert interlocutors. They were lived out through the spatially and temporally embodied occupation of urban space.